Mitigating the out-of-plane seismic vulnerability of unreinforced masonry façades with viscoelastic devices - Mora, Elesban Nochebuena (2023)
Surveys conducted after earthquakes have revealed that the most common and hazardous collapse mechanism observed in unreinforced masonry façades is the out-of-plane overturning. Traditional techniques such as tie rods, ring beams, and rigid slab-to-wall connections have been employed to enhance the seismic performance of unreinforced masonry (URM) buildings. However, there are alternative strengthening systems that may improve the performance compared to these conventional techniques. While passive energy dissipation (PED) devices are utilized in framed structures to mitigate dynamic response, their application to URM buildings remains limited. In this study, the effectiveness of three different strengthening techniques, namely rigid slab-to-wall connections, steel tie rods, and viscoelastic devices was investigated. A FEM model of a partial façade with a transversal wall was created to simulate the out-of-plane behaviour. Nonlinear dynamic analyses were conducted using recorded earthquakes as input. The performance of each technique was evaluated by comparing various parameters, namely displacements, base shear forces, plastic energy, and damage distribution. The results revealed that viscoelastic devices exhibited better performance in reducing displacements and mitigating the vulnerability of façade overturning.